Autopercepción del orientador educativo venezolano en la gestión de procesos vocacionales y del aprendizaje (2022)
This work shows results associated with the self-perception of the Venezuelan educational counselor in the management of vocational and learning processes. The research had a transactional and field design following a descriptive research. The population was conformed of resident and practicing educational counselors of the Republic of Venezuela, attached to the Ministry of Popular Power for Education and/or the Venezuelan Association of Counselors in any of the different chapters that comprise it. The sample was limited to 200 participating subjects. The data obtained were processed with the Statistical Package for the Social Sciences SPSS that uses statistical and mathematical processes. The information was organized in simple tables, and was represented visually by pie charts and bar graphs, according to its usefulness. The results show that the Venezuelan educational counselor perceives himself as an active agent capable of attending to a series of aspects and situations framed in the management of vocational and learning processes.